Analisis Literasi Keuangan, Pendapatan dan Sumber Pendapatan, Gaya Hidup dan Lingkungan Sosial terhadap Perilaku Keuangan Generasi Z - Henderika Kore Kudje; Irly Lestriani Haba Kore; Yesyurun Afonso; Yohanes P. Lian (AKUNTANSI 45, 2026)
This study aims to test and determine the influence of financial literacy, income and financial resources, lifestyle, and social factors on the spending behavior of generation Z students who study in the Accounting Study Program at two universities in Kupang City, namely Widya Mandira Catholic University (UNWIRA) and Nusa Cendana University (UNDANA). Generation Z is known to have unique characteristics in financial management, with spending preferences that tend to be digital and influenced by the academic and socio-economic environment. This study uses a quantitative approach with an associative design to analyze the relationship between variables. Data was collected through questionnaires distributed to accounting students at both campuses, then analyzed using descriptive and inferential statistical techniques. The results of the study are expected to show the extent to which financial literacy, income level, lifestyle, and social factors affect the spending behavior of Gen Z students.